Application Economic Order Quantity (EOQ) for Control of Raw Material Inventory - Melati, Mekar; Slamet, Achmad (Management Analysis Journal, 2019)
The purpose of this study was to determine the auxiliary raw material inventory control by Serabine and compare the method using Economic Order Quantity . The type of research is descriptive research with quantitative approach. The object this study is the amount of inventory raw materials, the number of purchases and the usage of raw materials. This study calculates the optimal inventory raw of coconut, rice flour and sugar using the EOQ method with calculation quantity of raw material purchase, frequency of purchase, safety stock, reorder point, and total inventory cost (TIC).This study shows that the use of the EOQ method is more optimal than using conventional methods. The use EOQ method can minimize the cost to ordering of raw materials and optimize carring costs. Total inventory cost of raw materials using EOQ method more efficient than using conventional methods it is shown by the company can save of the TIC for raw material Rp. 2,356,546.56, for coconut, Rp. 1,729,516.03 for rice flour, and Rp. 766,376.84. for sugar.